Medical Error Disclosure: An Entrustable Professional Activity During an Objective Standardized Clinical Examination for Clerkship Students - Rebecca Dougherty; Alice Fornari; Gino Farina; Doreen M. Olvet (Association of American Medical Colleges, 2024)
Introduction Most health care providers will be involved in a medical error during their careers. It is critical that future physicians receive formal training on error disclosure. Methods We designed a formative skills-based objective standardized clinical exam (OSCE) for fourth-year medical students to assess competence in disclosing an error during a required entrustable professional activity. Faculty observed the encounter and completed a checklist evaluating students' performance in communication skills and content knowledge. Students received immediate formative feedback. They then participated in a facilitated case-based experience, discussed the critical elements of disclosure, utilized role-play to reinforce skills, and reflected on self-care practices. Finally, students completed a survey evaluating their perception of the OSCE's impact on their disclosure knowledge, skills, and attitudes. Results Ninety-two students participated in the OSCE. Of those, 67 (73%) completed a retrospective pre/post survey assessing their disclosure knowledge, skills, and attitudes. Forty-one (62%) did not identify the error. Students who identified the error (26, 39%) were more likely to use the two-patient identifier than students who did not identify the error, χ2(1) = 13.3, p < .001. Self-reported comfort and confidence in disclosure improved, as did self-care practices (ps ≤ .005). Discussion Students agreed that health care providers should disclose an error and know how to do so. Student self-reported comfort in disclosure and knowledge of how to disclose and how to report an error all improved following the OSCE and structured debrief. The OSCE and case-based experience can be adapted for implementation in curricula about error disclosure.